AB0388 Sleep disturbances in inflammatory rheumatic diseases. (12th June 2018) - Addimanda, O.; Burattini, M.; Baldelli, L.; Chiaro, G.; Pignotti, E.; Provini, F.; Meliconi, R.
Abstract : Background: Inflammatory rheumatic joint diseases such as Ankylosing Spondylitis (AS) and Rheumatoid Arthritis (RA) have recently been found to be associated with sleep disturbances especially obstructive sleep apnoea. 1 2 Objectives: The aim of our study was to evaluate the occurrence of sleep disturbances, especially REM Sleep Behaviour Disorder (RBD), in inflammatory rheumatic diseases, (rheumatoid arthritis -RA and Spondyloarthritides -SpA). Methods: We enrolled 103 consecutive patients affected by inflammatory rheumatic diseases [RA (64, 62.1%) or SpA (39, 37.9%)]. Patients underwent a neurologic and psychopathological assessment, including identification of sleep disorders by means of the Pittsburgh Sleep Quality Index (PSQI), the Berlin and the REM sleep behaviour disorder (RBD) questionnaires, a structured interview on sleep terrors and sleep paralysis, Beck Depression Inventory (BDI-II) and the Spielberger State-Trait Anxiety Inventory (STAI). Statistical analysis was performed utilising SPSS software. Results: No significant differences were found between RA and SpA patients in age at diagnosis, disease duration, smoke habit, alcohol consumption, anamnestic comorbidities (especially metabolic diseases, anxiety or depression), disease activity/remission and biologic Disease Modifying Antirheumatic Drugs use. No differences demonstrated in BDI-II, STAI, PSQI and RBD questionnaires; only the Berlin Questionnaire showed significant differences (17.2% in RA vs 35.9% in SpA, p=0.036). No differences in sleep paralysis (10.9% in RA vs 7.7% in SpA, p=0.74) and sleep terrors (37.5% in RA vs 20.5% in SpA, p=0.0826) which were found to be increased if compared with general population (2.6%.) Conclusions: Our data show an increased prevalence of sleep terrors in rheumatic patients when compared to the general population although no differences were highlighted between RA and SpA; also increased risk of sleep apnoea (Berlin Questionnaire) has been demonstrated in patients with SpA compared with RA. References: [1] Aydin E, Bayraktar K, Turan Y, Omurlu I, Tastaban E, Sendur OF. Sleep quality in patients with ankylosing spondylitis. Rev Bras Reumatol2015;55:340–5. [2] Taylor-Gjevre RM, Nair BV, Gjevre JA. Obstructive sleep apnoea in relation to rheumatic disease. Rheumatology2013;52:15–21. [3] American Academy of Sleep Medicine. International Classification of Sleep Disorders, 3rd ed, American Academy of Sleep Medicine, Darien, IL 2014. Disclosure of Interest: None declared